Government Regulation and the Legal Environment of Business - Mayer, Don; Warner, Daniel; Siedel, George; Lieberman, Jethro K. (Open textbook library., 2012)
Mayer, Warner, Siedel and Lieberman's Government Regulation and the Legal Environment of Business is an up-to-date textbook that covers legal issues that students must understand in today's highly regulated business environment. The text is organized to permit instructors to tailor the materials to their particular approach. The authors take special care to engage students by relating law to everyday events with their clear, concise and readable style. After introductory chapters covering the legal environment of business, Government Regulation and the Legal Environment of Business provides students with context and essential legal concepts relating to contracts, consumer credit transactions, bankruptcy, intellectual property, securities regulation, regulation of real estate, antitrust, unfair trade practices, employment law and labor relations. The text provides the vocabulary and legal savvy they will need to talk in an educated way to customers, suppliers, employees, creditors, shareholders, government regulators and other stakeholders — and to their own lawyers.